The Need for Specialized Translators in the current Translation Market in Germany - Hennecke, Angelika (Universidad Pedagógica y Tecnológica de Colombia, 2017)
This article makes a brief description and examination of the labor market for translators in Germany. The impact of new technologies and forms of communication, such as the internet and other digital media, is taken into account. Experiences with this kind of qualification in Germany are described, with a special focus on the Master’s degree on Specialized Translation of the Cologne University of Applied Sciences (TH Köln). In this context, the lack of didactics for translation teaching and the implications of this are discussed, in order to prepare future translators for a growingly complex and challenging labor market.